PENURUNAN FUNGSI HATI TIKUS BETINA (Rattus norvegivus L) YANG DIINJEKSI WHITE VITAMIN C DOSIS TINGGI DALAM JANGKA WAKTU LAMA DITINJAU DARI KADAR SGPT, SGOT SERTA GAMBARAN HISTOLOGI HATI - Sudatri, Ni Wayan; Setyawati, Iriani; Suartini, Ni Made; Yulihastuti, Dwi Ariani (Metamorfosa: Journal of Biological Sciences, 2016)
This study aims to determine the side effects of high-dose injections of vitamin C in a long term against liver histology. This study used a completely randomized design (CRD) with different long treatments of vitamin C injection in various doses of P0 (control), P1 (30 days injection), P2 (50 days injection), P3 (70 days injection) and P4 (90 days injection). Parameters measured were plasma levels of SGPT and SGOT, the percentage of hydropic degeneration,  fatty degeneration, pyknotik nuclei, and necrosis of liver cells, and also inflammatory cell infiltration and sinusoid congestion. SGOT levels showed a significant differences (P=0,009) between the treatment and control group by ANOVA test. The Kruskal Wallis test showed that ALT levels were not significantly different (P=0,86), however, the levels of creatinine showed significant differences (P=0,002). The hydropic degeneration were not significantly different (P=0,054) by Kruskal Wallis test, whereas the fatty degeneration were significantly different (P=0,000) between the treatment and control groups by ANOVA test. Pyknotik nuclei and necrotic cells showed significant differences between the control and treatment with the P value of 0,016 and 0,01 respetively. The injected white vitamin C in high doses for long periods decreased the physiological functions of female mice liver.
Keywords: liver histology, SGPT, SGOT, white vitamin C, the female rats